Semantically Incorrect: Analysis of some Akan Constructions. - Appiah, Mr. George; OfosuMarfo, Dr. Charles (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
The use of particular constructions in Akan may be regarded as semantically incorrect through Feature Theory (e.g. Kaplan & Bresnan (1982)) and (semantic) feature analysis (e.g. Dalrymple et al. (1995), (Aitchison 2002)); i.e. they fail to conform to some semantic restrictions. We observe that, normally, this incorrectness is due to clash of features. In this paper, we identify some of such constructions in Akan, descriptively analyze them in terms of feature analysis, and proceed to provide the correct forms per proper feature description. Drawing clues from aspects of ethnography of communication theory (e.g. Gumperz (1972),Saville-Troike (2003)), however, we also strive to argue for the fact that these semantically incorrect or questionable constructions are accepted by the speakers of the language and that a semantic-defined yardstick cannot always solely be the determining factor of what is appropriate or not.